Simultaneous determination of three curcuminoids in Curcuma longa L. by high performance liquid chromatography coupled with electrochemical detection - Yuling Long; Wenpeng Zhang; Fang Wang; Zilin Chen (Elsevier, 2014)
A novel method for analysis of three active components curcumin, demethoxycurcumin and bisdemethoxycurcumin in Curcuma longa L. was developed by HPLC coupled with electrochemical detection. Three curcuminoids were well separated on a C18 column and detected with high sensitivity. A mobile phase containing acetonitrile and 10Â mM Na2HPO4âH3PO4 (pH 5.0) (50:50, v/v) was used. Good linearity was obtained in the range of 0.208â41.6, 0.197â39.4, and 0.227â114Â Î¼M for curcumin, demethoxycurcumin and bisdemethoxycurcumin respectively. The limit of detection reached up to 10â8Â M, which was lower than that by UV detection. The relative standard deviations (RSDs) ranged from 1.06% to 1.88% for intra-day precision and from 4.30% to 5.79% for inter-day precision, respectively. The proposed method has been applied in real herb sample and recoveries ranging from 86.3% to 111% were obtained. Keywords: Curcumin, High performance liquid chromatography, Electrochemical detection, Curcuma longa L.